2017
DOI: 10.1002/2016jc012199
|View full text |Cite
|
Sign up to set email alerts
|

Sea-ice thickness from field measurements in the northwestern Barents Sea

Abstract: The Barents Sea is one of the fastest changing regions of the Arctic, and has experienced the strongest decline in winter‐time sea‐ice area in the Arctic, at −23±4% decade−1. Sea‐ice thickness in the Barents Sea is not well studied. We present two previously unpublished helicopter‐borne electromagnetic (HEM) ice thickness measurements from the northwestern Barents Sea acquired in March 2003 and 2014. The HEM data are compared to ice thickness calculated from ice draft measured by ULS deployed between 1994 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 43 publications
0
29
0
Order By: Relevance
“…ERA-I is known to have an anomalously large fraction of liquid precipitation (rain) and thus low snowfall to precipitation ratio in the Arctic, especially during August-September (Dutra et al, 2011;Leeuw et al, 2015). The total precipitation accumulated along the buoy drift trajectories, during the cold season (from 15 August or 1 October until a buoy fails or until 30 April), was higher in ERA5 than in ERA-I for every buoy examined.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…ERA-I is known to have an anomalously large fraction of liquid precipitation (rain) and thus low snowfall to precipitation ratio in the Arctic, especially during August-September (Dutra et al, 2011;Leeuw et al, 2015). The total precipitation accumulated along the buoy drift trajectories, during the cold season (from 15 August or 1 October until a buoy fails or until 30 April), was higher in ERA5 than in ERA-I for every buoy examined.…”
Section: Discussionmentioning
confidence: 92%
“…The low SF / TP ratio and thus larger fraction of rainfall in ERA-I is known to be anomalous, and is likely due to the cloud physics scheme used (e.g. Dutra et al, 2011;Leeuw et al, 2015). In ERA-I, the split between liquid and ice in clouds is determined diagnostically as a function of temperature from −23 to 0 • C, with ice only below −23 • C and liquid only above 0 • C. In contrast, the IFS Cy41r2 used in ERA5 includes a prognostic microphysics scheme, with separate cloud liquid, cloud ice, rain and snow prognostic variables (Sotiropoulou et al, 2015; see also ECMWF IFS documentation -Cy41r2; https://www.ecmwf.int/sites/default/files/ elibrary/2016/16648-part-iv-physical-processes.pdf, last access: 4 March 2019).…”
Section: Comparison Of Precipitation and Snowfall From Era5 And Era-imentioning
confidence: 99%
“…Between 19 and 26 March, eight AEM flights were carried out by a helicopter based on the Norwegian research vessel Lance ( Fig. 13b; King et al, 2017). In contrast to the Beaufort Sea data, these data contain first-year ice only.…”
Section: Barents Sea March 2014mentioning
confidence: 99%
“…Field studies and direct observations allow the investigation of the composition of ice types , the amount and structure of the snow cover Webster et al, 2014), and the seasonal changes in ice and snow thickness Wang et al, 2016). Regional (e.g., Hansen et al, 2013;King et al, 2017;Renner et al, 2013Renner et al, , 2014 and local studies (Gerland et al, 2008) in the European sector of the Arctic Ocean have shown a thinning of sea-ice coherent with that documented on a pan-Arctic scale.…”
Section: Introductionmentioning
confidence: 99%